Validated KASP Markers for drought tolerance in cotton enable efficient trait selection and preliminary mechanism analysis - Wenju Gao; Hu Zhang; Qin Chen; Ning Wang; Jianbin Shi; Yibin Zhang; Qinghua Xu; Jieyin Zhao; Quanjia Chen; Gentu Yan (Plant Stress)
Drought stress poses a significant threat to global agriculture, making drought tolerance a key target in cotton breeding. In this study, 22 Kompetitive Allele-Specific PCR (KASP) markers were developed based on drought-related QTL intervals in upland cotton. A total of 502 core germplasm accessions were genotyped and evaluated for drought tolerance under controlled conditions. Phenotype–genotype association analysis identified 10 markers significantly associated with drought performance, among which markers 22079 and 22089 exhibited high selection accuracy (>85 %). Haplotype analysis further revealed that Hap8 showed 100 % accuracy in identifying drought-tolerant accessions. Key agronomic traits, including plant height (PH), effective fruit branch number (EFBN), effective boll number (EBN), single boll weight (SBW), and transpiration rate (Tr), were significantly correlated with drought tolerance and linked to the identified markers. Candidate gene prediction highlighted several drought-responsive genes, such as a Bacillus-like protease and a 14–3–3 protein. Functional exploration of the 14–3–3 gene through RNA sequencing, yeast two-hybrid screening, and Arabidopsis phenotyping supported its potential role in drought resistance. These validated KASP markers and gene candidates provide effective tools for marker-assisted selection (MAS) and lay a foundation for further investigation into the molecular mechanisms of drought tolerance in cotton.